Responsibility Mapping: How its implementation can contribute to better governance - Krambia-Kapardis, Maria (My University, 2018)
Governance describes the elements of organizational control and accountability that are necessary for the good management of any organization, private or public. The processes that are involved in Corporate Governance (CG) also play a key role in controlling corruption by promoting ethical behaviour and enhancing competence. In addition, the effective implementation of a good governance system decreases the risk of fraud by encouraging a work environment that is not conducive for such behaviour. Governance enables better monitoring and control of management and accountability of the board, which sets the tone at the top.
Keywords: Responsibility Mapping; comporate governance